TINJAUAN YURIDIS TANGGUNG JAWAB PERUSAHAAN PELAYARAN SEBAGAI PENGANGKUT ANGKUTAN LAUT BATUBARA MENURUT UNDANG UNDANG REPUBLIK INDONESIA NOMOR 17 TAHUN 2008 TENTANG PELAYARAN DI PELABUHAN SAMARINDA - Andrea Hasiholan (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
AbstractThe maritime sector is a very strategic field for Indonesia which is the largest archipelagic country in the world. As a developing country, Indonesia often makes buying and selling transactions, both in terms of goods entering or shipping goods. Transportation of goods by sea is one way to carry out sale and purchase transactions for large quantities of goods. Transportation of the goods is carried out both for domestic and overseas shipping. The transportation of goods by sea is included in the voyage regulated in Act Number 17 of 2008 concerning Shipping. In transporting goods by sea it is necessary to make an agreement between the sender and the carrier. A transportation agreement is a reciprocal agreement between the carrier and the sender, in which the carrier ties himself to carry out the transportation of goods and/or people from a certain place to a certain destination safely, while the sender commits himself to pay the transportation fee. The transportation agreement involves the sender or owner of the goods. This transportation agreement creates different rights, obligations, and responsibilities for each party. These rights, obligations, and responsibilities must be fulfilled as much as possible by each party. When negligence or default occurs that results in a loss, the injured party has the right to claim compensation. There are several ways to resolve compensation disputes in the transportation of goods by sea. The Indonesian government is expected to draft national legislation relating to Indonesian sea transportation. Because so far Indonesia has still used regulations adopted from the Netherlands which have also been long established.Keywords: Shipping, Sea Transportation. Coal.